User Engagement with A Multimodal Conversational Agent for Self-Care and Chronic Disease Management: A Retrospective Analysis. - Colakoglu, Selahattin; Durmus, Mustafa; Polat, Zeynep Pelin; Yildiz, Asli; Sezgin, Emre (Journal of Medical Systems, 2025)
Introduction: Understanding user engagement with conversational agents is key to their sustainable use in mobile health and improving patient outcomes. This retrospective study analyzed interactions with a multimodal conversational agent in the Albert Health app to identify usage patterns and barriers to long-term engagement in self-care and chronic disease management. Methods: We retrospectively analyzed interactions from 24,537 users of a Turkish-language mobile health app (between January 1, 2022, and December 31, 2023). Interactions with the app's multimodal conversational agent (voice and text) were categorized by demographics, interaction type, and engagement mode. Descriptive statistics summarized patterns, while Mann-Whitney U, Chi-square, and logistic regression identified group differences and predictors of sustainable engagement. Results: Most users were female (56%) and aged 30–45 (44%). The majority (92%) used general health programs, with only 8% in disease-specific ones. Common interaction types included health information (32%), small talk (20%), and clinical parameter logging (16%; e.g., blood pressure). Voice use was frequent in fallback (80%; unclear/ out-of-scope input), small talk (64%), and medication tasks (53%), while screen input was more common for clinical logging (61%) and health queries (59%). Engagement peaked in the first week and declined after 10 days. Sustainable engagement was associated with disease-specific program use (OR = 0.67, 95%CI: 0.60–0.74, p < 0.001), greater voice interaction (OR = 1.005, 95%CI: 1.004–1.006, p < 0.001), and a balanced mix of clinical and non-clinical use (OR = 1.56, 95%CI: 1.43–1.70, p < 0.05). Conclusions: This study highlights user preferences for voice interaction and health information access when using a multimodal conversational agent. The high rate of single-session users (58%) points to barriers to sustainable engagement, emphasizing the need for better user experience strategies.